Characterization of an Aging-Based Diagnostic Gene Signature and Molecular Subtypes With Diverse Immune Infiltrations in Atherosclerosis - Zhao, Lei; Lv, Fengfeng; Zheng, Ye; Yan, Liqiu; Cao, Xufen (Frontiers in Molecular Biosciences, 2022)
Objective: Advancing age is a major risk factor of atherosclerosis (AS). Nevertheless, the mechanism underlying this phenomenon remains indistinct. Herein, this study conducted a comprehensive analysis of the biological implications of ageing-related genes in AS. Methods: Gene expression profiles of AS and non-AS samples were curated from the GEO project. Differential expression analysis was adopted for screening AS-specific ageing-related genes. LASSO regression analysis was presented for constructing a diagnostic model and the discriminatory capacity was evaluated with ROC curves. Through consensus clustering analysis, ageing-based molecular subtypes were conducted. Immune levels were estimated based on the expression of HLAs, immune checkpoints and immune cell infiltrations. Key genes were then identified via WGCNA. The effects of CEBPB knockdown on macrophage polarization were examined with western blotting and ELISA. Furthermore, macrophages were exposed to 100 mg/L ox-LDL for 48 h to induce macrophage foam cells. After silencing CEBPB, markers of cholesterol uptake, esterification and hydrolysis, and efflux were detected with western blotting. Results: This study identified 28 AS-specific ageing-related genes. The ageing-related gene signature was developed, which could accurately diagnose AS both in the GSE20129 (AUC=0.898) and GSE43292 (AUC=0.685) datasets. Based the expression profiling of AS-specific ageing-related genes, two molecular subtypes were clustered, with diverse immune infiltration features. The molecular subtype-relevant genes were obtained with WGCNA, which were markedly associated with immune activation. Silencing CEBPB triggered anti-inflammatory M2-like polarization and suppressed foam cell formation. Conclusion: Our findings suggest the critical implications of ageing-related genes in diagnosing AS and modulating immune infiltrations.